2022
DOI: 10.1038/s41598-022-11512-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-based spatial distribution of workers is resilient to worker loss in a subterranean termite

Abstract: Elaborate task allocation is key to the ecological success of eusocial insects. Termite colonies are known for exhibiting age polyethism, with older instars more likely to depart the reproductive center to access food. However, it remains unknown how termites retain this spatial structure against external disturbances. Here we show that a subterranean termite Coptotermes formosanus Shiraki combines age polyethism and behavioral flexibility to maintain a constant worker proportion at the food area. Since this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…The previous study has demonstrated that the old‐age soldiers frequently protected the nest compared to young‐age soldiers under the artificial experiments in the termite Reticulitermes speratus (Yanagihara et al, 2018). It should also be noted that the age‐related task allocation could contribute to the colony maintenance under variable environments in the termite Coptotermes formosanus (Lee et al, 2022). Each individual experiences different tasks in the process of ageing, and the individual behavioural differences and resulting task allocation could be determined through individual experiences in some ants (Stroeymeyt et al, 2011; Tanaka et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous study has demonstrated that the old‐age soldiers frequently protected the nest compared to young‐age soldiers under the artificial experiments in the termite Reticulitermes speratus (Yanagihara et al, 2018). It should also be noted that the age‐related task allocation could contribute to the colony maintenance under variable environments in the termite Coptotermes formosanus (Lee et al, 2022). Each individual experiences different tasks in the process of ageing, and the individual behavioural differences and resulting task allocation could be determined through individual experiences in some ants (Stroeymeyt et al, 2011; Tanaka et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…There were no relationships between aggressive response, and body size and sexes in either soldiers or pseudergates in our study (Figures S1-S4 et al, 2018). It should also be noted that the age-related task allocation could contribute to the colony maintenance under variable environments in the termite Coptotermes formosanus (Lee et al, 2022).…”
Section: Possible Factors Underlying Context-dependent Defensive Beha...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that foraging termites display degrees of age polyethism, as older workers tend to forage further away from the central part of the nest than younger workers (Du et al, 2017;Su et al, 2017;Lee et al, 2021). It therefore explains why the demographic profile of a colony may vary among traps on any given sampling date, as the age cohort of foragers are not homogeneously distributed throughout the colony foraging territory (Lee et al, 2022). For a given colony with multiple monitored foraging sites, it can therefore be inferred that a trap with a majority of old workers is located further away from the central part of the nest than a trap with a majority of relatively young workers (Shimizu, 1962;Su et al, 2017;Lee et al, 2022).…”
Section: Developmental Pathway Context To Interpret Colony Age Demogr...mentioning
confidence: 99%
“…It therefore explains why the demographic profile of a colony may vary among traps on any given sampling date, as the age cohort of foragers are not homogeneously distributed throughout the colony foraging territory (Lee et al, 2022). For a given colony with multiple monitored foraging sites, it can therefore be inferred that a trap with a majority of old workers is located further away from the central part of the nest than a trap with a majority of relatively young workers (Shimizu, 1962;Su et al, 2017;Lee et al, 2022). In mature colonies of C. formosanus, soldiers (S) are produced from various worker pathways through a presoldier stage (PS), which depends on the availability of workers at the time they initiate differentiation into soldiers: W 1 → PS 2 → S 2 , W 2 → PS 3 → S 3 , and W 3 → PS 4 → S 4 .…”
Section: Developmental Pathway Context To Interpret Colony Age Demogr...mentioning
confidence: 99%